1980
DOI: 10.1210/endo-107-6-1699
|View full text |Cite
|
Sign up to set email alerts
|

Formation of [Des-Asp1]Angiotensin I by the Perfused Rat Lung*

Abstract: Bioassay studies have indicated that angiotensin I (Ang I), but not angiotensin II (Ang II), is degraded by the intact lung. The present study was an attempt to isolate and quantify pulmonary metabolites of Ang I. The pulmonary vascular bed of the rat was isolated and perfused at 4-6 ml/min (< 20 mm Hg) with oxygenated Krebs buffer containing 5% bovine serum albumin. [3H-Leu10]Ang I (3-10 ng) was administered, and pulmonary effluent samples were collected every 15 sec for 5 min. Peptides were isolated by Dowex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1981
1981
1994
1994

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…From qualitative studies in sheep reported earlier, 31 -M it was suggested that the concentration of All in venous blood was small. Using more sophisticated methodology and especially recovery tracers, we have shown here that the arterial and central venous profiles are very similar.…”
Section: Model Of Steady-state Angiotensin Metabolismmentioning
confidence: 94%
“…From qualitative studies in sheep reported earlier, 31 -M it was suggested that the concentration of All in venous blood was small. Using more sophisticated methodology and especially recovery tracers, we have shown here that the arterial and central venous profiles are very similar.…”
Section: Model Of Steady-state Angiotensin Metabolismmentioning
confidence: 94%